The Sociology of Religion in a Post-Colonial Era: Towards Theoretical Reflexivity - Spickard, James V. (Religions, 2019)
This article makes two points. First, it argues that sociology, like all knowledge, is shaped, though not determined, by its historical-cultural origins. Early sociology arose in 19th-century Europe and its core concepts were shaped by that eraboth in what they reveal about society and what they hide. We now realize this, so we sociologists of religion need to examine our inherited concepts to understand those concepts' limitations. We also need to include an analysis of the way the current historical-cultural situation shapes sociology today. This is the theoretical reflexivity called for in the title. Second, the article argues that expanding sociology's conceptual canon to include insights from other historical-cultural locations is more than just an ethical matter. It is also epistemological. Sociology does not make progress unless it includes insights from as many standpoints as possible. This does not mean that all insights are equal. It does mean that all have the potential to improve sociological understanding. Whether or not they actually do so is a matter for the scientific process to decide.